2022
DOI: 10.1016/j.radcr.2021.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous subarachnoid hemorrhage due to arteriovenous malformation mimicking migraine: A case report

Abstract: Subarachnoid hemorrhage (SAH) due to Arteriovenous Malformation (AVM) is a rare emergency case, which is often misdiagnosed as migraine. Here we present a case of SAH due to AVM that mimics migraine. A 41-year-old man came with headaches that radiated to the neck, worsened in the last week, accompanied by nausea, vomiting, photophobia, and a history of intermittent headaches for the previous 2 years. Physical examination was within normal limits, initial laboratory tests showed leukocytosis, and CT scan was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The laboratory findings of that study revealed thrombocytopenia, low fibrinogen levels and elevated D-dimer levels, while antibodies against platelet factor 4 were positive in the majority of assays performed ( 2 ). However, it should be noted that sometimes, in certain age groups of patients, these symptoms may be associated with congenital vascular anomalies or drug abuse ( 3 , 4 ). Carbon monoxide, viper envenomation, methylenedioxymethamphetamine have been reported to lead to acute cerebral venous thrombosis ( 5-7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory findings of that study revealed thrombocytopenia, low fibrinogen levels and elevated D-dimer levels, while antibodies against platelet factor 4 were positive in the majority of assays performed ( 2 ). However, it should be noted that sometimes, in certain age groups of patients, these symptoms may be associated with congenital vascular anomalies or drug abuse ( 3 , 4 ). Carbon monoxide, viper envenomation, methylenedioxymethamphetamine have been reported to lead to acute cerebral venous thrombosis ( 5-7 ).…”
Section: Introductionmentioning
confidence: 99%